Africa - Murray Jocelyn 1929 (New York : Facts on File, 1990)
Describes the history of Africa and examines the tribes and cultures of its countries.
Includes bibliographical references (p. 92) and index.
Keywords: Africa -- History -- Juvenile literature; Africa -- Civilization -- Juvenile literature; Africa